Prevalence of congenital anomalies and related factors in live births in Zahedan, Southeast of Iran: A cross-sectional study - Azam Asemi-Rad; Zahra Heidari; Hamidreza Mahmoudzadeh-Sagheb; Yousef Mehdipour; Bita Moudi; Nadia Sheibak; Saeid Ebrahimi (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: The term congenital anomalies (CAs) refers to structural or functional abnormalities at the time of conception. Approximately 12 deaths related to congenital disabilities occur in every 10,000 babies born. Objective: This study aimed to evaluate the prevalence and associated factors of single and multiple CAs in live births in Zahedan, Southeast Iran. Materials and Methods: This cross-sectional study was conducted on 59,087 live births in a referral hospital in Zahedan located in the southeast of Iran from 2009 to 2019. All live births were examined by pediatricians and the CAs and categorized based on the international classification of diseases. Results: Of 59,085 live births, at least 883 had a significant anomaly, and the prevalence rate of CAs was about 149 per 10,000. Anomalies of the nervous (24.1%) and cardiovascular systems (21.10%) were the most frequent, occurring in 213 and 187 of the live births, respectively. Spina bifida is the most common anomaly of the central nervous system. The most common anomalies in the cardiovascular system were unspecified heart malformations (17.1%), cardiovascular malformations (18.7%), and patent ductus arteriosus (11.7%). Significant correlations were found between the parent's consanguinity marriage, the mother's age, an existing anomaly in the family, and relatives in single and multiple CAs (p = 0.02, p = 0.02, p < 0.001, p = 0.01, respectively). Conclusion: The prevalence of CAs was 149 per 10,000 live births. The highest prevalence of CAs was related to the central nervous system. Increasing the public's knowledge about fetal defects can reduce the prevalence of CAs.